The attitude of the religious authority in AL Najaf from the Constitutional Revolution in Iran - Khwaiter, Muhammed Hashem (Al-Adab Journal, 2019)
The Constitutional Revolution and one of the most important political events in Iran early twentieth century, sometimes known as known (conditional) or as it is called in the Iranian literature as the ((Musharoutit)) is a term of the condition and the conditions, which means that the ruling should be judged according to the terms written in the Constitution , and the adherence to and compliance with these conditions. It contributed to a variety of factors in turn do this revolution, it was the most important of a number of revolutionary uprisings and precursors such as witnessed by the Iran revolution such as tobacco uprising (1891-1892) and the reformist intellectual movement that had a clear role in the wake of the Iranian people about the constitutional life . Iran has emerged in a number of senior hardworking who have called for reform of the bad situation in Iran and an end to tyranny Qajari and put an end to foreign domination on the capabilities of the country, especially Britain and Czarist Russia dominance, which enjoyed privileges and wide on the Iranians account.